Urban Farming Sebagai Pilar Ketahanan Pangan di Kawasan Pinggiran Kota: Praktik Dan Dampaknya di Desa Ciherang, Bogor - Erna Ernawati; Testa Pradia Nirwana; Nurhayati Nurhayati; Ali Alamsyah Kusumadinata (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
Urban farming is an important strategy in facing the challenges of food security and land constraints in urban areas. This study aims to describe the practices and benefits of community-based urban farming activities in Ciherang Village, Dramaga District, Bogor Regency. The research method uses a qualitative and participatory descriptive approach with data collection techniques through interviews, direct observations, and literature studies. The results of the study show that the pressure of land conversion is the main driver for the community to optimize yard land and sleeping land through various innovative methods such as hydroponics, verticulture, and cultivation in polybags. The activity, which is coordinated by farmer groups or PKK, is carried out independently through the stages of preparing planting media, planting, routine maintenance, and harvesting together. The analysis revealed that urban farming in Ciherang Village provides multidimensional benefits, namely: (1) increasing household food security through the availability of fresh and healthy food; (2) providing economic benefits from spending savings to potential surplus sales; (3) improve the quality of the environment; and (4) strengthening social cohesion and interaction in the community. It was concluded that group-based urban farming is an effective and sustainable solution to create local food independence and empower communities in suburban areas that experience land scarcity.